Inovasi The Gade Clean & Gold Pada Bank Sampah Mutiara Di Kota Pekanbaru - Gushilda, Disa; Yuliani, Febri; Asari, Hasim (JPAP: Jurnal Penelitian Administrasi Publik, 2022)
This research is motivated by the existence of a new innovation related to waste management which aims to change the mindset of the community towards waste so that people know that waste can also be useful and has value and to increase citizens' interest in waste banks that can provide benefits to the community, one of which is in the form of  long term investment.  And with the innovation of this waste bank, it can reduce environmental pollution caused by the accumulation of indiscriminate garbage. The purpose of this study is to find out the innovation that is the Gade Clean and Gold at the Pearl Waste Bank of Pekanbaru City and identify the factors that hinder the innovation.  This study uses a qualitative research method approach.  The research data was obtained directly from the results of observations and interviews with informants and interactive data analysis. The results of this study explain that the innovation of the gade clean and gold at the pearl waste bank in the city of Pekanbaru is not optimal, this can be seen from several inhibiting indicators in the form of limited facilities and infrastructure such as press machines, chopping machines and waste storage warehouses and limited human resources that make  the waste at the pearl bank that is received is not managed by the waste bank but is resold to the vendor